Current data on the characterization of oral clefts in Brazil Informações atuais sobre a caracterização das fissuras orofaciais no Brasil - José Alberto de Souza Freitas; Gisele da Silva Dalben; Milton Santamaria Júnior; Patrícia Zambonato Freitas (Brazilian Oral Research, 2004)
This study aimed at investigating the current distribution of the several types of clefts among the patients receiving treatment at the Hospital for Rehabilitation of Craniofacial Anomalies (HRAC-USP), Bauru, Brazil, for the first time during the year 2000. A total of 803 unoperated patients with cleft lip and/or palate, with or without additional malformations, with no recognizable syndromes, who came to the HRAC-USP for enrollment for treatment during the year 2000. A predominance of complete cleft lip and palate, either unilateral or bilateral, was observed (37.1%), followed by isolated cleft palate (31.7%) and isolated cleft lip (28.4%). A discrete relationship between cleft palate and the female gender was noticed (53%), and males were more affected by the other types of clefts (around 60%). The findings revealed a predominance of complete clefts of the primary and secondary palate, the treatment of which is more complex, and whose frequency is greater in males. Foi objetivo do presente estudo investigar a distribuição atual dos vários tipos de fissuras entre pacientes que compareceram ao Hospital de Reabilitação de Anomalias Craniofaciais (HRAC-USP), Bauru, Brasil, pela primeira vez, no ano de 2000. No total, 803 pacientes não operados com fissura de lábio e/ou palato, com ou sem malformações adicionais, sem síndromes reconhecíveis, compareceram ao HRAC-USP para inscrição para tratamento durante o ano de 2000. Foi observada predominância de fissura completa de lábio e palato, unilateral ou bilateral (37,1%), seguida pela fissura de palato isolada (31,7%) e fissura de lábio isolada (28,4%). Foi notada uma relação discreta entre a fissura de palato e o gênero feminino (53%), sendo o gênero masculino mais afetado pelos outros tipos de fissuras (cerca de 60%). Os achados revelaram uma predominância de fissuras completas do palato primário e secundário, cujo tratamento é mais complexo, e uma maior ocorrência no gênero masculino.